Iron-deficiency Anaemia in Infants and Pre-school children in Three Racial groups in Cape Town - Lanzkowsky, Philip (Department of Medicine, 2020)
Iron-deficiency anemia is probably the commonest deficiency disease in infants and children throughout the world today. This prevalence is indeed surprising as the condition can be readily detected. Moreover, iron medication is cheap and for many years has been known to be effective in the prephylaxis and treatment of iron-deficiency anemia. In America, reportedly the most health-conscious of all countries, Guest and Brown (1957) have reported that the incidence, in at least one centre, is as high today as it was twenty years ago. If this is true in a country where practicing physicians are well primed about the importance of adequate nutrition, it is likely that in less-privileged communities there is probably greater failure to recognize or correct this deficiency state.